Corrosion inhibition of 6061 aluminium alloy in acidic media by honey - Mohd Azzizul, Chamingan (2010)
The corrosion inhibition of aluminum and its alloys in acidic solution is the subject of the tremendous technological importance due to the increased in industrial applications of these materials. Aluminum and its alloy, however are reactive material and prone to corrosion. Inhibitor is the most practical method to protect metal against corrosion. Most of the corrosion inhibitors are synthetic chemicals, expensive and very hazardous to environment. Therefore, it should be reduced use to protect environmentally and human in the future. For this project, 6061 Aluminum Alloy in 5% H2SO4 was evaluated by using weight loss method and electrochemical techniques. This study investigated the effect of variation concentration of honey as inhibitor to the corrosion behavior of 6061 Aluminum alloy in the acidic solution. In weight loss method, the samples were immersed in the solution for the duration of 28 days. The samples were weighted before exposure and through the cleaning process using Nitric Acid after the immersion test. The mass loss after cleaning cycle was analyzed in term of corrosion rates. The microscopic examination was conducted by using metallurgical microscope. Potentiodynamic polarization was employed for electrochemical measurement by using WonATech potentiostat. The samples were mounted by resin before it attached as working electrode. The results showed that addition of natural honey retards the rate of dissolution and hence inhibits the corrosion of the 6061 Aluminum Alloy in 5% H2SO4 solution. The inhibitor efficiency increased with increasing of honey concentration for both methods. It was found that, the uniform corrosion occur to the surface of Aluminum alloy in acidic solution. The tafel plot from the potentiodynamic polarization also showed that the honey significantly decrease the corrosion potential (Ecorr) and current density (icorr) and concurrently, increase the surface coverage. The adsorption of natural honey on the me